Different effects of anesthetic isoflurane on caspase-3 activation and cytosol cytochrome c levels between mice neural progenitor cells and neurons - Yiying eZhang; Chuxiong ePan; Chuxiong ePan; Xu eWu; Xu eWu; Yuanlin eDong; Deborah eCulley; Gregory eCrosby; Tianzuo eLi; Zhongcong eXie (Frontiers in Cellular Neuroscience, 2014)
Commonly used anesthetic isoflurane has been reported to promote Alzheimer’s disease (AD) neuropathogenesis by inducing caspase-3 activation. However, the up-stream mechanisms of the isoflurane’s effects remain largely to be determined. Specifically, there is a lack of a good model/system to elucidate the underlying mechanism of the isoflurane-induced caspase-3 activation. We therefore set out to assess and compare the effects of isoflurane on caspase-3 activation in neural progenitor cells (NPCs) and in primary neurons from wild-type (WT) and AD transgenic (Tg) mice. The NPCs and neurons were obtained, cultured and then treated with either 2% isoflurane or under control condition for six hours. The NPCs or neurons were harvested at the end of the treatment and were subjected to Western blot analysis. Here we showed for the first time that the isoflurane treatment induced caspase-3 activation in neurons, but not in NPCs, from either WT or AD Tg mice. Consistently, the isoflurane treatment increased cytosol levels of cytochrome c, a potential up-stream mechanism of isoflurane-induced caspase-3 activation in the mice neurons, but not NPCs. Finally, the isoflurane treatment induced a greater casapse-3 activation in the neurons, but not the NPCs, from AD Tg mice than those from WT mice. These data demonstrated that investigation and comparison of isoflurane’s effects between mice NPCs and neurons would serve as a model/system to determine the underlying mechanism by which isoflurane induces caspase-3 activation. These findings would promote more research to investigate the effects of anesthetics on AD neuropathogenesis and the underlying mechanisms.